Between sacrum and prophanum: Authority, knowledge, democracy - Broda, Marian (Creativity Studies, 2009)
An often underestimated reference point of great importance for understanding of the contemporary social and political consciousness is the rooting of such consciousness in the structures of archaic thinking. In this light, the experience of power becomes a component of a more universal experience of sacrum: the establishment of an order, a result of the invasion of holiness – the epiphany – is considered as simultaneous establishment of the world and the truth. Sacrum, power, leadership, order, identity, truth, authority and rightness remain integrally interconnected and only the power able to satisfy such total expectations receives the real legitimization. It does not become a party to “a contract” governing the rights and obligations of each side, but rather – in a manner typical for religious or quasi‐religious act, one unconditionally gives up to such power, commits to it. The contents rooted in the archaic experience of sacrum, disguised by the historically younger cultural layers are stemming from deep layers and structures of the social conscience. In particular, in the time of crisis they reveal their presence on multiple occasions, helping various Sons of Lights on their road to power. Such persons, in the eyes of their worshippers hold the monopoly for an alleged higher, exclusive and integral Truth. The authoritarian order, de facto excluding the possibility of an authentic dialogue, becomes an alternative for the democratic citizen society – resting upon the assumptions that the individuals are free, mature and independent, willing to take the responsibility for their own fate and for the matters of their communities. Tarp sacrum ir profanum: autoritetas, žinojimas, demokratija Santrauka. Archainio mąstymo struktūros yra labai svarbus, tačiau nepakankamai įvertintas veiksnys, apmąstant šiuolaikinę socialinę ir politinę sąmonę. Archainio mąstymo aspektu valdžios patirtis tampa kur kas universalesnės sacrum patirties sudedamąja dalimi. Tvarkos įsteigties, šventenybės įsiveržties pasekmė – epifanija – čia nagrinėjama kaip vienalaikė pasaulio ir tiesos steigtis. Sacrum, valdžia, lyderystė, tvarka, tapatumas, tiesa, autoritetas ir teisingumas išlieka neatsiejamai susieti, ir tik per valdžią galima realizuoti tikro teisėtumo lūkesčius. Taip teisėtumas tampa ne būdu manipuliuoti abiejų pusių teisėmis ir įsipareigojimais, bet religiniu ar kvazireliginiu aktu, besąlygiškai įsipareigojančiu ir paklūstančiu valdžiai. Turinius, įšaknytus archainėje sacrum patirtyje, užkloja naujesnieji kultūriniai sluoksniai, besipriešinantys gilesniesiems socialinės sąmonės sluoksniams ir struktūroms. Krizės metu tie turiniai atsiskleidžia daugeliu atvejų, įkvėpdami pačius įvairiausius Šviesos Sūnus, siekiančius valdžios. Tokie asmenys savo garbintojų akyse saugojo aukštesniosios, išskirtinės ir vienatinės Tiesos monopolį. Autoritarinė tvarka, de facto steigianti autentiško dialogo galimybę, tampa demokratinės pilietinės visuomenės alternatyva, paremta prielaidomis, esą individai yra laisvi, brandūs ir nepriklausomi, gebantys prisiimti atsakomybę už savo pačių ir savųjų bendruomenių likimus. Reikšminiai žodžiai: autoritetas, demokratija, žinojimas, valdžia, profanum, sacrum, tiesa. First Published Online: 14 Oct 2010